2015
DOI: 10.1136/bmjopen-2014-006420
|View full text |Cite
|
Sign up to set email alerts
|

What the public knows and wants to know about medicines research and development: a survey of the general public in six European countries

Abstract: ObjectivesTo explore public knowledge of, and interest in, learning more about medicines R&D in six European countries.DesignOnline survey of 6931 members of the public across Europe.MethodsThe survey formed part of a public omnibus survey. A quota sampling approach was used with quotas set according to national census data on age, gender and government region. The survey explored the public's knowledge and awareness of medicines R&D, their interest in learning more and the perceived influences on this.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 14 publications
0
27
0
2
Order By: Relevance
“…According to our results, Finns estimate their knowledge on medicines R&D lower than British, French, German, Italian and Polish respondents (14). This is rather surprising as traditionally Finns have expressed strong interest towards science and research (17,18,19) and as health literacy is also a part of the national school curricula in Finland (20).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…According to our results, Finns estimate their knowledge on medicines R&D lower than British, French, German, Italian and Polish respondents (14). This is rather surprising as traditionally Finns have expressed strong interest towards science and research (17,18,19) and as health literacy is also a part of the national school curricula in Finland (20).…”
Section: Discussionmentioning
confidence: 58%
“…As an earlier involvement in clinical research increased patients self-reported knowledge and willingness to learn more about certain aspects of medicines R&D and HTA, our results imply that participation into a clinical research has been an educating and perhaps also an empowering experience for the participants (14).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Группа исследователей под руководством S. Parsons [6] опубликовала в 2015 г. результаты масштабного опроса с участием 6931 респондента, проведенного на территории 6 европейских стран, целью которого было выяснить уровень осведомленности по всем аспектам разработки лекарственных средств, а также связь уровня осведомленности с социодемографическими и другими факторами. Результаты исследования показали, что только каждый пятый (n=1436; 22%) опрошенный считает, что хорошо информирован о КИ, при этом авторы обнаружили, что мужчины чаще, чем женщины, сообщали о глубоких знаниях касательно разработки лекарственных средств (17 против 15%), а уровень осведомленности снижался с возрастом (от 19% в возрастной группе 18-24 лет до 11% в группе старше 65 лет).…”
Section: осведомленность обществаunclassified